2014
DOI: 10.1097/bcr.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Virtual Reality on Adolescent Pain During Burn Wound Care

Abstract: The objective of this study was to compare the effect of virtual reality to passive distraction and standard care on burn treatment pain in adolescents.This single-blinded, randomized controlled study enrolled 30 adolescents who were 10 to 17 years of age from the burn clinic of a large children's hospital. After providing informed consent/assent, these participants were randomly assigned to one of three groups during wound care: standard care, passive distraction watching a movie, or virtual reality (VR) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
227
1
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(266 citation statements)
references
References 58 publications
19
227
1
19
Order By: Relevance
“…Trials during laceration repair for children in the ED (Ha & Kim, 2013) and during physical therapy for children and adolescent burn patients (Schmitt et al, 2011) showed improved pain relief with distraction versus no distraction. Sophisticated multimodal distraction (e.g., educational device, virtual reality) decreased pain intensity relative to standard distraction (e.g., television, videos, stories, toys, soothing) in studies of children or adolescents with burns (Brown, Kimble, Rodger, Ware, & Cuttle, 2014; Jeffs et al, 2014; Kipping, Rodger, Miller, & Kimble, 2012; Miller, Rodger, Kipping, & Kimble, 2011). An abundance of evidence supports the use of distraction techniques for reducing pain and potentially reducing the need for anxiolytics and opioids, particularly after burns (Drahota et al, 2012; Jeffs et al, 2014).…”
Section: Nonpharmacologic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials during laceration repair for children in the ED (Ha & Kim, 2013) and during physical therapy for children and adolescent burn patients (Schmitt et al, 2011) showed improved pain relief with distraction versus no distraction. Sophisticated multimodal distraction (e.g., educational device, virtual reality) decreased pain intensity relative to standard distraction (e.g., television, videos, stories, toys, soothing) in studies of children or adolescents with burns (Brown, Kimble, Rodger, Ware, & Cuttle, 2014; Jeffs et al, 2014; Kipping, Rodger, Miller, & Kimble, 2012; Miller, Rodger, Kipping, & Kimble, 2011). An abundance of evidence supports the use of distraction techniques for reducing pain and potentially reducing the need for anxiolytics and opioids, particularly after burns (Drahota et al, 2012; Jeffs et al, 2014).…”
Section: Nonpharmacologic Optionsmentioning
confidence: 99%
“…Distraction techniques (e.g., movies, virtual reality) focus patient attention and limit the nervous system's ability to process pain stimuli (Jeffs et al, 2014). These techniques have been shown to effectively relieve pain in adults (Drahota et al, 2012), and other studies have focused on their efficacy in children and adolescents.…”
Section: Nonpharmacologic Optionsmentioning
confidence: 99%
“…[15,16]). Specifically, VR technology has been used successfully in burn care settings, with results of multiple studies indicating reductions in pain associated with routine burn-related procedures such as wound care [17], wound debridement [18], dressing changes [19], and physical therapy [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been well established b u r n s x x x ( 2 0 1 5 ) x x x -x x x that the use of distraction during medical procedures significantly reduces pain and anxiety experienced by children [9,19]. There have been multiple studies confirming the effectiveness of specific CLT devices and techniques in burns; for example virtual reality, music therapy, or use of the Ditto TM device (Diversional Therapy Technologies, Brisbane, Australia) [7,10,11,[20][21][22][23]. In our Burn Unit, not only have we found that specific techniques and devices appear beneficial, but the role of a CLTP has anecdotally also had a significant impact on the reduction of pain and anxiety experienced by children with acute burns.…”
Section: Discussionmentioning
confidence: 97%